Accounting students' perception of the accounting profession. - Goh, Ko Hin. (2008)
This study shows that exposure to accounting courses results in more negative perception of students towards accounting as a profession and as a career. The results also indicate that students who have completed their Professional Attachment programme have more positive perception towards accounting than those who have not.